SYNCHRONIC STUDY OF HARMFUL AND RECURRENT PHENOMENA IN PROFESSIONAL LANGUAGE - López-Gómez, Eugenio Jesús (2020)
The authors of this work have been doing for a long time a synchronic study of emerging language phenomena that have become socially recurrent, up to the point of being stereotyped. This situation is also in Medical College from Villa Clara, Cuba, whose professionals, of course, are part of it. Hence, the objective is: to analyze some harmful and recurrent phenomena in current professional language. There were applied mainly the theoretical methods of analysis-synthesis, induction-deduction; besides, the empirical methods of observation and document review. Along with it, the systematic exchange with professionals of the Institution has been useful. The most signifi cant phenomena detected are: indiscriminate dividing of the noun in male and female genders ―welcome…―, tendency to verbalization of nouns and adjectives ―to open (opening); to make negative (negative)…―; inadequate syntactic fragmentation of verbal periphrases of infi nitive ―to say that…, to highlight that…―. These facts contribute, in the fi rst two cases, to increase stereotyped verbosity and, in the third, to logic rupture of expression omitting the auxiliary verb and use only the infi nitive ―somewhat similar to aboriginal language―. In short, the analyzed phenomena are very harmful in social communication; but, what is more, in university professionals speaking, who unconscious and gradually worsen their expression. This contradicts the rules and characteristics of scientific language and the style of their professional language image. Keywords: professional language ‒ recurrent, noxious phenomena ‒ stereotype